2019
DOI: 10.1177/2158244019876297
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Hiding Behaviors and Team Creativity: The Contingent Role of Perceived Mastery Motivational Climate

Abstract: The present study explains how different factors of knowledge hiding (e.g., evasive, playing dumb, and rationalized) influence on team creativity. Drawn on social exchange theory, the present study theorizes that factors of knowledge hiding have a negative relationship with team creativity, and absorptive capacity mediates this relationship. In addition, the perceived mastery motivational climate (PMMC) as a moderator attenuates the negative relationship between factors of knowledge hiding and team creativity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 73 publications
(162 reference statements)
6
86
0
Order By: Relevance
“…Although organizations put in a lot of effort to foster knowledge-sharing activities among individuals (Wang and Noe, 2010), the success of such effort relies on the employee's willingness and intention to share 3 Accepted Version -Journal of Organizational Change Management DOI 10.1108/JOCM-06-2019-0174 2016; Pan et al 2016). Some scholars have emphasised that KH is different from knowledge hoarding (Connelly et al 2012;Bari et al 2019) and that KH is merely the failure to share knowledge (Connelly et al 2012). This may arise because people are not aware of others' need for the knowledge (Gagne et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although organizations put in a lot of effort to foster knowledge-sharing activities among individuals (Wang and Noe, 2010), the success of such effort relies on the employee's willingness and intention to share 3 Accepted Version -Journal of Organizational Change Management DOI 10.1108/JOCM-06-2019-0174 2016; Pan et al 2016). Some scholars have emphasised that KH is different from knowledge hoarding (Connelly et al 2012;Bari et al 2019) and that KH is merely the failure to share knowledge (Connelly et al 2012). This may arise because people are not aware of others' need for the knowledge (Gagne et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, rationalized hiding could enhance interpersonal relationships between the person who was requested and the one who made the request. Further investigation of the influence of different attributes of knowledge hiding on team creativity showed that evasive hiding and playing dumb significantly and negatively influenced team creativity, while rationalized hiding did not significantly impact on team creativity (Bari et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 91%
“…The informed consent of the participants was implied through investigation achievement. The authors also did a comparison between late and early responses (Bari, Abrar, Shaheen, et al, 2019;Dillman, 2011). After comparison, it was confirmed that there was not a significant difference between the early and late respondents.…”
Section: Sample and Data Collection Proceduresmentioning
confidence: 99%